The cost of implanting a cemented versus cementless total knee arthroplasty. (July 2019) - Lawrie, C. M.; Schwabe, M.; Pierce, A.; Nunley, R. M.; Barrack, R. L.
Abstract : Aims: The aim of this study was to compare the actual cost of a cemented and cementless total knee arthroplasty (TKA) procedure. Materials and Methods: The cost of operative time, implants, cement, and cementing accessories were included in the overall cost of the TKA procedure. Operative time was determined from a previously published study comparing cemented and cementless implants of the same design. The cost of operative time, implants, cement, and cementing accessories was determined from market and institutional data. Results: Mean operative time for cemented TKA was 11.6 minutes longer for cemented TKA than cementless TKA (93.7 minutes (sd 16.7) vs 82.1 minutes (sd 16.6); p = 0.001). Using a conservative published standard of $36 per minute for operating theatre time cost, the total time cost was $418 higher for cementing TKA. The cost of cement and accessories ranged from $170 to $625. Overall, the calculated cost of cemented TKA is $588 to $1043, depending on technique. The general increased charge for cementless TKA implants over cemented TKA implants was $366. Conclusion: The overall procedural cost of implanting a cementless TKA is less than implanting a cemented TKA. Cost alone should not be a barrier to using cementless TKA. Cite this article: Bone Joint J 2019;101-B(7 Supple C):61–63